Antigenic and Genetic Characterization of Lipoprotein LppQ from Mycoplasma mycoides subsp. mycoides SC - Abdo, El-Mostafa (American Society for Microbiology, 2000)
Lipoprotein LppQ, a predominant 48-kDa antigen, and its corresponding gene, lppQ, were characterized in Mycoplasma mycoides subsp. mycoides SC, the etiological agent of contagious bovine pleuropneumonia. The lppQ gene is specific to M. mycoides subsp. mycoides SC and was found in the type strain and in field strains isolated in Europe, Africa, and Australia, as well as in vaccinal strains. LppQ is encoded as a precursor with a consensus sequence for prokaryotic signal peptidase II and a lipid attachment site. The leader sequence shows significant prominent transmembrane helix structure with a predicted outside-to-inside helix formation capacity. The N-terminal domain of the mature LppQ was shown to be surface exposed. It induced a strong, specific, early, and persistent immune response in naturally and experimentally infected animals. The C-terminal domain of LppQ possesses an integral membrane structure built up of repeated units, rich in hydrophobic and aromatic amino acids, which have a pore formation potential. A recombinant peptide representing the N-terminal domain of LppQ was obtained by site-directed mutagenesis of nine Mycoplasma-specific TGA (Trp) codons into universal TGG (Trp) codons and expression in Escherichia coli hosts. It was used for serodetection of cattle infected with M. mycoides subsp. mycoides SC, in which it was detected postinfection for significantly longer than conventional serological test reactions.